Crystal structure of Hop2–Mnd1 and mechanistic insights into its role in meiotic recombination. Issue 7 (3rd March 2015) - Kang, Hyun-Ah; Shin, Ho-Chul; Kalantzi, Alexandra-Styliani; Toseland, Christopher P.; Kim, Hyun-Min; Gruber, Stephan; Peraro, Matteo Dal; Oh, Byung-Ha
Abstract: In meiotic DNA recombination, the Hop2−Mnd1 complex promotes Dmc1-mediated single-stranded DNA (ssDNA) invasion into homologous chromosomes to form a synaptic complex by a yet-unclear mechanism. Here, the crystal structure of Hop2−Mnd1 reveals that it forms a curved rod-like structure consisting of three leucine zippers and two kinked junctions. One end of the rod is linked to two juxtaposed winged-helix domains, and the other end is capped by extra α-helices to form a helical bundle-like structure. Deletion analysis shows that the helical bundle-like structure is sufficient for interacting with the Dmc1-ssDNA nucleofilament, and molecular modeling suggests that the curved rod could be accommodated into the helical groove of the nucleofilament. Remarkably, the winged-helix domains are juxtaposed at fixed relative orientation, and their binding to DNA is likely to perturb the base pairing according to molecular simulations. These findings allow us to propose a model explaining how Hop2−Mnd1 juxtaposes Dmc1-bound ssDNA with distorted recipient double-stranded DNA and thus facilitates strand invasion.